The Effects of Neurolinguistic Programming (NlP) Methods Towards Students’ Speaking Skill - Mildan Arsdan Fidinillah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The objective of this research is to investigate the effects of Neurolinguistic Programming (NLP) method towards students’ speaking skill at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan. This research was conducted at Madrasah Ibtidaiyah Sa’adatuddarain 2 Tangerang Selatan from April 15th 2016-July 15th 2016. By using purposive sampling technique, 60 out of 300 students of grade V in school year 2015-2016 were chosen. The method used was a survey with a correlational technique. The instrument included one test to analyze the data quantitatively. Test is used to assess the students’ speaking skill. There is a positive and significant impact of students that learning using NLP method in the ability of speaking English. Furthermore, ? = 0.05, df = 19, and t-table = 1.73, while tcount = 9, 26. Thus tcount> ttable, this means that H0is rejected and H1is accepted, As conclusion, NLP method affects positively and significantly to the students’ speaking English ability compared with conventional method. Key words: Neurolinguistic Programming (NLP) method, speaking skill, English learning